Determinants of walking fitness in patients with heart failure attending cardiac rehabilitation. Issue 1 (27th February 2019) - Doherty, Patrick; Harrison, Alexander Stephen; Hossain, Rashed
Abstract : Introduction: Patients with heart failure (HF) attending cardiac rehabilitation (CR) benefit in terms of improved quality of life, physical fitness and reduced hospital admissions. Too few patients with HF attend CR and little data exist on the characteristics of those who do especially in respect of physical fitness. This study evaluates the extent by which clinical and demographic factors determine walking fitness in patients with a primary diagnosis of HF. Methods: Clinical data from the British Heart Foundation National Audit of Cardiac Rehabilitation identified 1519 patients with HF who completed an incremental shuttle walk test (ISWT). Stepwise regression accounting for age, gender and multiple potential confounders assessed their contribution to total walking distance. Results: Mean age was 64.5 (SD 12.70) years with a range of ISWT distances across gender and associated comorbidities from 215 to 282 m. Walking distance reduced by 4.9 m for each year increase in age above mean age (p<0.001). After accounting for confounders, females walked 42.1 m less than males (p≤ 0.001). Pulmonary disease and the existence of depression was associated with a 39.3 and 52.2 m reduction in walking distance, respectively. Body mass index >30 was associated with 28.5 m reduction in walking distance (p<0.001). HF severity failed to improve the regression model fit or achieve significance in the analysis Conclusions: Age, gender and the presence of pulmonary disease or depression were highly significant factors in predicting walking fitness in patients with HF. The study also produced a set of reference values based on these four factors to aid the interpretation of walking fitness in patients with HF.